2006
DOI: 10.1007/s10802-006-9028-9
|View full text |Cite
|
Sign up to set email alerts
|

Bias and Accuracy of Children's Perceptions of Peer Acceptance: Prospective Associations with Depressive Symptoms

Abstract: Are depressive symptoms in middle childhood associated with more or less realistic social self-perceptions? At the beginning and end of the school year, children in grades 3 through 5 (n=667) rated how much they liked their classmates, predicted the acceptance ratings they would receive from each of their classmates, and completed self-report measures of perceived acceptance and depressive symptoms. Accuracy of perceived acceptance was indexed by the mean difference between pairs of predicted and received rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 38 publications
2
36
1
Order By: Relevance
“…These results support findings linking rejection sensitivity to loneliness and social anxiety (Downey, Bonica, London, & Paltin, in press), perhaps because of the nervous affect associated with anticipating rejection. The scar effect found here is also consistent with studies finding that depressive symptoms predict social self-perceptions (Kistner et al, 2006;Rohde et al, 1990). The interactional framework for depression suggests that the behaviors of depressed individuals lead them to get rejected by others (Coyne, 1976(Coyne, , 1999.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results support findings linking rejection sensitivity to loneliness and social anxiety (Downey, Bonica, London, & Paltin, in press), perhaps because of the nervous affect associated with anticipating rejection. The scar effect found here is also consistent with studies finding that depressive symptoms predict social self-perceptions (Kistner et al, 2006;Rohde et al, 1990). The interactional framework for depression suggests that the behaviors of depressed individuals lead them to get rejected by others (Coyne, 1976(Coyne, , 1999.…”
Section: Discussionsupporting
confidence: 88%
“…This cognitive vulnerability hypothesis posits that the presence of certain cognitive features (e.g., low self-esteem, negative attributional style) predisposes individuals to a higher vulnerability for later depression or adjustment problems when the individual is exposed to stressful circumstances. Although some studies have found that cognitive features predict future depressive symptoms, others have revealed influences of depression on subsequent cognitions, such as attributional style and social perceptions (Kistner, David-Ferdon, Repper, & Joiner, 2006;Nolen-Hoeksema, Girgus, & Seligman, 1992;Rohde, Lewinsohn, & Seeley, 1990). It is possible that experiencing a depressive episode or a period of depressive symptoms can lead individuals to develop a more pessimistic explanatory style or to be more sensitive to rejection, features that remain after the depression subsides.…”
Section: Directionality Of the Association Between Cognitive Style Anmentioning
confidence: 99%
“…These aims are consistent with recent calls for researchers to consider adolescents' views of their relationships with peers when examining dimensions of peer group relationships and mental health [Hymel and Franke, 1985;Kistner et al, 2006;Lopez and DuBois, 2005]. The expected mental health symptoms associated with problematic peer relationships have been found when adolescents report their own awareness of their peer relationship problems and express negative attitudes toward their peers and their peers' behaviors.…”
Section: Adolescents' Perceptions Of Their Peerssupporting
confidence: 79%
“…Reciprocal relations are also illustrated in a study of third and fifth graders (Kistner et al, 2006). Similarly, inaccurate self-perception predicts increases in depressive symptoms and depressive symptoms, in turn, predict decreased accuracy in self-perception (Kistner et al, 2006). Academic overestimation predicts depression at many grade levels, but the reverse relation yields stronger effects (Cole, 1999).…”
Section: Reviewmentioning
confidence: 85%
“…Among fourth graders followed prospectively through sixth grade, depression symptoms predict change in children's negative selfevaluations (McGrath & Repetti, 2002). Reciprocal relations are also illustrated in a study of third and fifth graders (Kistner et al, 2006). Similarly, inaccurate self-perception predicts increases in depressive symptoms and depressive symptoms, in turn, predict decreased accuracy in self-perception (Kistner et al, 2006).…”
Section: Reviewmentioning
confidence: 86%